2017
DOI: 10.1186/s40856-017-0013-6
|View full text |Cite|
|
Sign up to set email alerts
|

Barriers to women’s representation in academic excellence and positions of power

Abstract: Nearly for half a century women's advancement in the workplace has been in a debate. Women's under-represented in higher education institutions and universities across the globe, and especially in the most powerful or influential posts, is well established. Despite gender equality commitments and women's educational attainment, still, they are underrepresented. Regions and countries may vary in term of culture, achievements and development, but barriers for women's representation in academia are surprisingly s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 34 publications
(37 reference statements)
2
33
0
2
Order By: Relevance
“…When they are given a leadership role, they try to strike a balance between their publications and other leadership responsibilities. As a result, their research suffers and most women professors opt out of such roles (Morley et al, 2017; Yousaf and Schmiede, 2017). Many women perceive such roles as a set of unattractive administrative functions requiring a 24/7 commitment.…”
Section: Discussionmentioning
confidence: 99%
“…When they are given a leadership role, they try to strike a balance between their publications and other leadership responsibilities. As a result, their research suffers and most women professors opt out of such roles (Morley et al, 2017; Yousaf and Schmiede, 2017). Many women perceive such roles as a set of unattractive administrative functions requiring a 24/7 commitment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, women face a sticky floor in their careers which leads men to get promoted faster and have faster access to higher positions. The aforementioned is confirmed by Yap andKonrad (2009), Hejase et al (2014) and Yousaf and Schmiede (2017).…”
Section: Resultsmentioning
confidence: 66%
“…While we were not able to identify speci c studies tackling gender barriers and KTE, it may be explained through the literature exploring challenges that women face in academia (23,24,31). A previous study indicated that men faculty members were able to positively engage in research and obtain funding while women found it harder to balance between undergraduate education and research efforts (32). Women not only publish less than men, they also still face challenges to get to decision making positions.…”
Section: Discussionmentioning
confidence: 92%